Question
upstudy study bank question image url

Solve \( 3 x^{2}+2 x-5=0 \)

Ask by Gray Howell. in Nigeria
Jan 11,2025

Upstudy AI Solution

Tutor-Verified Answer

Answer

The solutions are \( x = 1 \) and \( x = -\frac{5}{3} \).

Solution

To solve the quadratic equation \( 3x^{2} + 2x - 5 = 0 \), you can use either **factoring** or the **quadratic formula**. Below are both methods: --- ### **Method 1: Factoring** 1. **Write the equation in standard form:** \[ 3x^{2} + 2x - 5 = 0 \] 2. **Find two numbers that multiply to \( a \times c = 3 \times (-5) = -15 \) and add to \( b = 2 \):** The numbers are **5** and **-3** because: \[ 5 \times (-3) = -15 \quad \text{and} \quad 5 + (-3) = 2 \] 3. **Rewrite the middle term using these numbers:** \[ 3x^{2} + 5x - 3x - 5 = 0 \] 4. **Factor by grouping:** \[ (3x^{2} + 5x) - (3x + 5) = 0 \\ x(3x + 5) -1(3x + 5) = 0 \] 5. **Factor out the common binomial factor:** \[ (3x + 5)(x - 1) = 0 \] 6. **Set each factor equal to zero and solve for \( x \):** \[ 3x + 5 = 0 \quad \Rightarrow \quad x = -\frac{5}{3} \\ x - 1 = 0 \quad \Rightarrow \quad x = 1 \] **Solutions:** \[ x = 1 \quad \text{and} \quad x = -\frac{5}{3} \] --- ### **Method 2: Quadratic Formula** For any quadratic equation of the form \( ax^{2} + bx + c = 0 \), the solutions are given by: \[ x = \frac{-b \pm \sqrt{b^{2} - 4ac}}{2a} \] 1. **Identify the coefficients:** \[ a = 3, \quad b = 2, \quad c = -5 \] 2. **Plug the coefficients into the quadratic formula:** \[ x = \frac{-2 \pm \sqrt{2^{2} - 4 \times 3 \times (-5)}}{2 \times 3} \] 3. **Calculate the discriminant (\( \Delta \)):** \[ \Delta = 2^{2} - 4 \times 3 \times (-5) = 4 + 60 = 64 \] 4. **Take the square root of the discriminant:** \[ \sqrt{64} = 8 \] 5. **Find the two solutions:** \[ x = \frac{-2 + 8}{6} = \frac{6}{6} = 1 \\ x = \frac{-2 - 8}{6} = \frac{-10}{6} = -\frac{5}{3} \] **Solutions:** \[ x = 1 \quad \text{and} \quad x = -\frac{5}{3} \] --- Both methods yield the same solutions: \[ \boxed{x = 1 \quad \text{and} \quad x = -\dfrac{5}{3}} \]

Answered by UpStudy AI and reviewed by a Professional Tutor

error msg
Explain
Simplify this solution

The Deep Dive

To solve the quadratic equation \( 3x^{2} + 2x - 5 = 0 \), we can use the quadratic formula: \[ x = \frac{-b \pm \sqrt{b^2 - 4ac}}{2a} \] Here, \( a = 3 \), \( b = 2 \), and \( c = -5 \). First, we calculate the discriminant: \[ b^2 - 4ac = 2^2 - 4 \cdot 3 \cdot (-5) = 4 + 60 = 64 \] Now, we can substitute back into the quadratic formula: \[ x = \frac{-2 \pm \sqrt{64}}{2 \cdot 3} = \frac{-2 \pm 8}{6} \] This gives us two solutions: 1. \( x = \frac{-2 + 8}{6} = \frac{6}{6} = 1 \) 2. \( x = \frac{-2 - 8}{6} = \frac{-10}{6} = -\frac{5}{3} \) So, the solutions to the equation \( 3x^{2} + 2x - 5 = 0 \) are \( x = 1 \) and \( x = -\frac{5}{3} \). Remember, finding the roots of quadratics is useful not just in math classes but also in numerous fields like physics, engineering, and economics, where understanding how variables interact can lead to smarter decisions! Plus, double-checking your work is vital! Common mistakes include overlooking minus signs or miscalculating the discriminant. Avoid these traps by keeping your arithmetic precise and organized!

Related Questions

Latest Algebra Questions

Try Premium now!
Try Premium and ask Thoth AI unlimited math questions now!
Maybe later Go Premium
Study can be a real struggle
Why not UpStudy it?
Select your plan below
Premium

You can enjoy

Start now
  • Step-by-step explanations
  • 24/7 expert live tutors
  • Unlimited number of questions
  • No interruptions
  • Full access to Answer and Solution
  • Full Access to PDF Chat, UpStudy Chat, Browsing Chat
Basic

Totally free but limited

  • Limited Solution
Welcome to UpStudy!
Please sign in to continue the Thoth AI Chat journey
Continue with Email
Or continue with
By clicking “Sign in”, you agree to our Terms of Use & Privacy Policy